Cordycepin affects Streptococcus mutans biofilm and interferes with its metabolism - Yidan Shao; Wenyan Zhu; Shanshan Liu; Kai Zhang; Yu Sun; Yudong Liu; Tingchi Wen; Yingxue Zou; Qingwei Zheng (BMC Oral Health)
Abstract Background Streptococcus mutans (S. mutans) contributes to caries. The biofilm formed by S. mutans exhibits greater resistance to drugs and host immune defenses than the planktonic form of the bacteria. The objective of this study was to evaluate the anti-biofilm effect of cordycepin from the perspective of metabolomics. Methods The minimum inhibitory concentration (MIC) was determined to evaluate the antimicrobial effect of cordycepin on planktonic S. mutans. The 24-h biofilm was treated with 128 µg/mL of cordycepin for 10 min at the 8- or 20-h time points. Biofilm biomass and metabolism were assessed using crystal violet and MTT assays and cordycepin cytotoxicity was evaluated in human oral keratinocytes (HOK) using CCK-8 assays. The live bacterial rate and the biofilm volume were assessed by confocal laser scanning microscopy. Metabolic changes in the biofilm collected at different times during with cordycepin were analyzed by metabolomics and verified by quantitative real-time PCR. Results The results showed that treatment with 128 µg/mL cordycepin reduced both the biomass and metabolic activity of the biofilm without killing the bacteria, and cordycepin at this concentration showed good biocompatibility. Metabolomics analysis showed that differentially abundant metabolites following cordycepin treatment were mainly related to purine and nucleotide metabolism. After immediate treatment with cordycepin, genes related to purine and nucleotide metabolism were downregulated, and the levels of various metabolites changed significantly. However, the effect was reversible. After continuing culture for 4 h, the changes in genes and most metabolites were reversed, although the levels of 2’-deoxyadenosine, 2’-deoxyinosine, and adenine remained significantly different. Conclusions Cordycepin has the effect of anti-biofilm of S. mutans, mainly related to purine and nucleotide metabolism.